Sampling effort and its allocation in the Lincoln–Petersen experiment: A hierarchical approach - Chin, Su Na; Antony Overstall; Dankmar Bohning (Elsevier B.V., 2026)
Capture-recapture methods are widely used for estimating population sizes in ecological and epidemiological studies, yet the optimal allocation of sampling effort often remains underexplored. This study explores sampling efforts in a hierarchical framework that subdivides each capture occasion in a Lincoln–Petersen experiment into multiple sub-occasions, allowing for flexible resource allocation. When detection probabilities are equal across occasions, an even split minimizes variance; when probabilities differ, maximizing the joint detection probability is essential. A pseudo-Bayesian approach is also proposed to address scenarios with unknown catchabilities. Detailed simulation studies validate the theoretical findings and demonstrate the framework’s robustness. The resulting guidelines offer practical insights for designing more efficient capture-recapture experiments and improving population size estimates.